Isolation of pulmonary veins using a thermoreactive implantable device with external energy transfer: Evaluation in a porcine model. Issue 6 (4th May 2018) - Boussy, Tim; Vandecasteele, Tim; Vera, Lisse; Schauvliege, Stijn; Philpott, Matthew; Clement, Eli; van Loon, Gunther; Willenz, Udi; Granada, Juan F.; Stone, Gregg W.; Reddy, Vivek Y.; Van Langenhove, Glenn
Abstract: Background: Pulmonary vein isolation (PVI) is a well‐established method for the treatment of symptomatic paroxysmal atrial fibrillation, but is only partly successful with a high rate of electrical reconnection. We introduce a novel technique in which PVI is accomplished by noninvasive heating of a dedicated thermoresponse implant inserted into the pulmonary veins (PV), demonstrated in a porcine model. Methods: A self‐expanding nitinol‐based implant was positioned in the common inferior PV of 11 pigs, using a fluoroscopy‐guided transatrial appendage approach. Ablation was performed through contactless energy transfer from a primary extracorporal coil to a secondary heat ring (HR) embedded in the proximal part of the implant. Electrophysiological conduction was assessed prior to and postablation, and at 3 months. Histological samples were obtained acutely (n = 4) and after 3 months (n = 7). Results: In total, 13 PV implants were successfully positioned in the inferior PVs of 11 animals. Ablation was performed without injury of adjacent structures. PVI and bidirectional block was electrophysiologically confirmed in all cases immediately at the time of implantation and 3 months later in seven chronic animals in whom testing was repeated. Marked evidence of ablation around the proximal HR was evident at 3 months postprocedure, with scar tissue formation and only mild neointimal proliferation. Conclusions: Successful PVI can be obtained by external electromagnetic heat transfer to a novel pulmonary vein implant.